Dog Man. Vol. 5, Lord of the fleas - Pilkey, Dav (New York Scholastic Press, 2018)
When a new bunch of baddies bust up the town, Dog Man is called into action -- and this time he isn't alone. With a cute kitten and a remarkable robot by his side, our heroes must save the day by joining forces with an unlikely ally: Petey, the World's Most Evil Cat. But can the villainous Petey avoid vengeance and venture into virtue?
Comic Strips
1
Keywords: Cartoons and comics; Comic books, strips, etc